Preterm Infant-Associated Clostridium tertium, Clostridium cadaveris, and Clostridium paraputrificum Strains: Genomic and Evolutionary Insights. (29th September 2017) - Kiu, Raymond; Caim, Shabhonam; Alcon-Giner, Cristina; Belteki, Gusztav; Clarke, Paul; Pickard, Derek; Dougan, Gordon; Hall, Lindsay J.
Abstract: Clostridium species (particularly Clostridium difficile, Clostridium botulinum, Clostridium tetani and Clostridium perfringens ) are associated with a range of human and animal diseases. Several other species including Clostridium tertium, Clostridium cadaveris, and Clostridium paraputrificum have also been linked with sporadic human infections, however there is very limited, or in some cases, no genomic information publicly available. Thus, we isolated one C. tertium strain, one C. cadaveris strain and three C. paraputrificum strains from preterm infants residing within neonatal intensive care units and performed Whole Genome Sequencing (WGS) using Illumina HiSeq. In this report, we announce the open availability of the draft genomes: C. tertium LH009, C. cadaveris LH052, C. paraputrificum LH025, C. paraputrificum LH058, and C. paraputrificum LH141. These genomes were checked for contamination in silico to ensure purity, and we confirmed species identity and phylogeny using both 16S rRNA gene sequences (from PCR and in silico) and WGS-based approaches. Average Nucleotide Identity (ANI) was used to differentiate genomes from their closest relatives to further confirm speciation boundaries. We also analysed the genomes for virulence-related factors and antimicrobial resistance genes, and detected presence of tetracycline and methicillin resistance, and potentially harmful enzymes, including multiple phospholipases and toxins. The availability of genomic data in open databases, in tandem with our initial insights into the genomic content and virulence traits of these pathogenic Clostridium species, should enable the scientific community to further investigate the disease-causing mechanisms of these bacteria with a view to enhancing clinical diagnosis and treatment.